Pemberdayaan Masyarakat Melalui Pelatihan Pengelolaan Keuangan Keluarga Sebagai Upaya Untuk Meningkatkan Ketahanan Ekonomi Keluarga di Kelurahan Curug Kecamatan Bogor Barat - Ariyani, Nafiah (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2019)
Every family must have good knowledge about family financial management so that they can utilize their sources of income wisely in order to meet the needs for the realization of a prosperous family. The need for this knowledge will be greater especially in disadvantaged families where their income is very limited. Community service activities are intended to provide knowledge to underprivileged families about how to manage family finances appropriately through training and mentoring. The target partners of this activity are housewives from underprivileged families who often do not think long and wisely in managing family financial expenses. The activity was carried out in Curug Sub-District, West Bogor District, Bogor City. The training was conducted with lecture methods, tutorials, brainstorming and discussion. After participating in the training, it is expected that partners can develop a family budget based on their income and expenses determined by priority scale. Other groups that this activity wants to reach, partners will be encouraged to have the desire to save for better family welfare in the future.